Bilinguals' Existing Languages Benefit Vocabulary Learning in a Third Language. Issue 1 (10th August 2016) - Bartolotti, James; Marian, Viorica
Abstract: Learning a new language involves substantial vocabulary acquisition. Learners can accelerate this process by relying on words with native‐language overlap, such as cognates. For bilingual third language learners, it is necessary to determine how their two existing languages interact during novel language learning. A scaffolding account predicts transfer from either language for individual words, whereas an accumulation account predicts cumulative transfer from both languages. To compare these accounts, 20 English‐German bilingual adults were taught an artificial language containing 48 novel written words that varied orthogonally in English and German wordlikeness (neighborhood size and orthotactic probability). Wordlikeness in each language improved word production accuracy, and similarity to one language provided the same benefit as dual‐language overlap. In addition, bilinguals' memory for novel words was affected by the statistical distributions of letters in the novel language. Results indicate that bilinguals utilize both languages during third language acquisition, supporting a scaffolding learning model. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris‐database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .